2012
DOI: 10.1007/s00011-012-0466-2
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of C-reactive protein as a marker of early post-infarct left ventricular systolic dysfunction

Abstract: ObjectiveTo assess the usefulness of in-hospital measurement of C-reactive protein (CRP) concentration in comparison to well-established risk factors as a marker of post-infarct left ventricular systolic dysfunction (LVSD) at discharge.Materials and methodsTwo hundred and four consecutive patients with ST-segment-elevation myocardial infarction (STEMI) were prospectively enrolled into the study. CRP plasma concentrations were measured before reperfusion, 24 h after admission and at discharge with an ultra-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…In a study published by Swiatkiewicz et al, multivariate analysis demonstrated CRP concentration at discharge to be an independent marker of early postinfarction left ventricular dysfunction (odds ratio of 1.38, 95 % confidence interval 1.01-1.87; p < 0.04), which proves that higher levels of CRP upon admission identifies patients with worse outcomes and suggests that high hsCRP levels may identify patients who will have poorer results after reperfusion, or may be more likely to have ventricular remodeling and enlargement after hospital discharge (20). Similarly, in a recently published study by Perlas et al, high levels of hsCRP upon admission were found to correlate with an increase in cardiovascular risk on short term (21).…”
Section: Discussionmentioning
confidence: 95%
“…In a study published by Swiatkiewicz et al, multivariate analysis demonstrated CRP concentration at discharge to be an independent marker of early postinfarction left ventricular dysfunction (odds ratio of 1.38, 95 % confidence interval 1.01-1.87; p < 0.04), which proves that higher levels of CRP upon admission identifies patients with worse outcomes and suggests that high hsCRP levels may identify patients who will have poorer results after reperfusion, or may be more likely to have ventricular remodeling and enlargement after hospital discharge (20). Similarly, in a recently published study by Perlas et al, high levels of hsCRP upon admission were found to correlate with an increase in cardiovascular risk on short term (21).…”
Section: Discussionmentioning
confidence: 95%
“…Ultrasensitive methodologies for detecting free CRP in human serums are required. The most common approaches in analyzing CRP are enzyme-linked immunosorbent assay (ELISA), immunofluorescence, and so forth [3]. However, most of usual methods are time consuming, labor intensive, and hazardous to health or require highly qualified personnel and sophisticated instrumentation [46].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the potential value of CRP for the prediction of long-term LVSD and HF in patients with STEMI undergoing PCI and guideline-based therapies has not been definitely assessed [14,27]. Previous studies have been limited by heterogenous populations with acute coronary syndromes that were frequently untreated with PCI, small sample size, a lack of multiple high-sensitivity CRP measurements, absence of neurohormonal activation assessment, lack of long-term monitoring of LVEF and HF, and omission of long-term LVSD and HF as clinical endpoints [14,[16][17][18][21][22][23][24][25][26][27][28][29][30][31][32][33][34].The purpose of this study was to assess the value of high-sensitivity CRP in a homogenous population of patients with first STEMI undergoing primary PCI and guideline-based therapies for predicting the risk of: (i) LVSD at 6 months after hospital discharge (LVSD 6M ), which was the primary study endpoint; and (ii) the need for hospitalization for HF in patients with LVSD 6M in long-term multi-year follow-up, which was the secondary study endpoint. This secondary endpoint was chosen because hospitalization for HF is associated with subsequent increase in risk of mortality [8].We performed a single-center prospective cohort study with rigorous selection criteria, adequate sample size, and long-term follow-up data based on multiple assessment time-points: baseline, 24 h, and discharge during index hospitalization for STEMI, 1 month and 6 months after discharge, and long-term multi-year follow-up.…”
mentioning
confidence: 99%
“…At present, the potential value of CRP for the prediction of long-term LVSD and HF in patients with STEMI undergoing PCI and guideline-based therapies has not been definitely assessed [14,27]. Previous studies have been limited by heterogenous populations with acute coronary syndromes that were frequently untreated with PCI, small sample size, a lack of multiple high-sensitivity CRP measurements, absence of neurohormonal activation assessment, lack of long-term monitoring of LVEF and HF, and omission of long-term LVSD and HF as clinical endpoints [14,[16][17][18][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
mentioning
confidence: 99%